(Digital) tools as professional and generational identity badges in the Chinese creative industries - Liboriussen, Bjarke (Sage, 2015)
Animators, architects, designers, and others active in the Chinese creative industries are expert users of tools, both analog and digital. Performances of expert tool use (the wearing of professional identity badges) are strategic ways of signaling creativity understood as sets of skills and character traits essential for attracting work projects but also for professional identity formation. Analogue tools are generally associated with creative openness and fluidity whereas digital tools are discursively constructed as a technological other to the analogue. ‘Older’ creatives (born before 1980) tend to apply some of the media-inflected discourse around the balinghou generation (born 1980–1989) to their younger competitors, including an assumed affinity with digital media and technologies (the pinning on of a generational identity badge). Such generational assumptions can have the effect of reinforcing project hierarchies and denying expert users of digital tools their claims to creativity.